2017
DOI: 10.2147/ijn.s139602
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 nanoparticle penetrating the blood–brain barrier to improve the cerebral function of diabetic rats complicated with cerebral infarction

Abstract: Diabetic cerebral infarction is with poorer prognosis and high rates of mortality. Ginsenoside Rg1 (Rg1) has a wide variety of therapeutic values for central nervous system (CNS) diseases for the neuron protective effects. However, the blood–brain barrier (BBB) restricts Rg1 in reaching the CNS. In this study, we investigated the therapeutic effects of Rg1 nanoparticle (PHRO, fabricated with γ-PGA, L-PAE (H), Rg1, and OX26 antibody), targeting transferrin receptor, on the diabetes rats complicated with diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Rg1 nanoparticles were developed to overcome the blood-brain barrier (BBB)-mediated restriction of Rg1 to reach the CNS. At a high concentration, Rg1 nanoparticles can penetrate the BBB to reduce the cerebral infarction volume and promote neuronal recovery in vivo [ 144 ]. In addition, nanoparticle formulation of Rg3 offered neuroprotective activity in an AD model.…”
Section: Prospects For Delivery and Clinical Study Of Ginseng Componementioning
confidence: 99%
“…Rg1 nanoparticles were developed to overcome the blood-brain barrier (BBB)-mediated restriction of Rg1 to reach the CNS. At a high concentration, Rg1 nanoparticles can penetrate the BBB to reduce the cerebral infarction volume and promote neuronal recovery in vivo [ 144 ]. In addition, nanoparticle formulation of Rg3 offered neuroprotective activity in an AD model.…”
Section: Prospects For Delivery and Clinical Study Of Ginseng Componementioning
confidence: 99%
“…Several animal studies have found that ginseng processed products or individual ginsenosides regulate blood glucose in diabetic mouse or rat models, accompanied by regulating the expression of TNF-α, eNOS [46,53,56], suggesting that diabetes is associated with inflammation, and effective modulation by ginseng on inflammation may be able to prevent the development of insulin resistance. Recently, Shen et al reported that Rg1 released in brain tissue using nano-drug delivery systems reduced the volume of cerebral infarction and improved neural recovery in diabetic rats with cerebral infarction [59], indicating that the hypoglycemic effect of Rg1 may be regulated through the central nervous system. Additionally, in an STZ-induced type 1 diabetic rat model, ginsenoside Rh2 reduced fasting blood glucose and improved cardiac function via enhancing PPAR-δ signaling in diabetic rats with cardiac fibrosis [60].…”
Section: Potential Mechanisms Of the Anti-diabetic Effect Of Ginsengmentioning
confidence: 99%
“…The tubes were formed according to the report [25,26]. In conclusion, RBE4 cells (1 Â 10 4 ) were inoculated into 24 well plate coated with 50 ll Matrigel and cultured with 400 ll ECM culture medium with 10% FBS and 1% P/S in the presence of 10 ll PBS (Control group), Meg3-control plasmid (2 lg, CP group), Meg3 plasmid (2 lg, Meg3 group) or MPO (MPO group, containing 2 lg plasmid), respectively.…”
Section: Tube Formation Assaymentioning
confidence: 99%
“…Rat cerebral infarction model was made as described before [25]. Briefly, the rats were anesthetized with 3% pentobarbital sodium (30 mg/kg).…”
Section: Rat Cerebral Infarction Modelmentioning
confidence: 99%
See 1 more Smart Citation